Perancangan Sistem Informasi Purchasing PT QAM Berbasis Web Dengan Metode Waterfall - Kiong, Ritchie; Antonius, Antonius; Willay, Thommy (Universitas Multi Data Palembang, 2025)
In the rapidly developing digital era, technology can help a company improve efficiency, productivity, and competitiveness in business. PT QAM's purchasing information system still relies on simple computerization, namely recording, processing, and storing locally. Simple computerization that is implemented has the potential to reduce operational effectiveness in goods requests and goods purchase data collection. This study aims to develop a responsive web-based purchasing information system so that it can be accessed directly by staff through each staff's device, either via mobile phone or via computer. The methods applied in this study include system development using the iterative waterfall model and a web-based integrated system along with the use of the MySQL database as data storage, allowing real-time data collection of goods requests and purchases. In the development of this study, Unified Modeling Language (UML) modeling was used. The implementation of this system is expected to be able to record data effectively, store data safely, and facilitate report printing. Thus, this system has the potential to increase the productivity and effectiveness of the company.